Contribution of Growth Centres in Agricultural Development of Imphal Valley During 1990s. - P. Robinson Singh, L. Sunil Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the process of development of an area, the locational view of growth impulses is equally important because there are many processes which are accelerated through growth points. In the historical perspective, the socio-economic development is continuous process through which change in the economic landscape can be observed. In the present context, when we are going to discuss the role of growth centres in agricultural development with reference to Imphal valley, it can be said that the valley is economically passing through its initial stage of development where growth points are also emerging with their diverse functional nature. No doubt, the emerging locational patterns of these specific growth points would be playing a significant role for accelerating the developmental processes on its economic landscape and faster growth of the area.